2011
DOI: 10.2169/internalmedicine.50.5228
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Advanced Atrioventricular Block by Cilostazol

Abstract: We describe a case of advanced atrioventricular (AV) block, in which treatment with cilostazol was effective in recovering the AV conduction. The patient was referred to our hospital for close examination of the advanced AV block and permanent pacemaker implantation. Although the patient had experienced thirddegree AV block with occasional AV synchrony for more than two days, the AV conduction completely recovered after treatment with oral cilostazol at 200 mg/day. Here we discuss the possible mechanism of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Recent studies have reported the effectiveness of orally administered cilostazol, a phosphodiesterase III inhibitor, in treating bradyarrhythmia in humans and animals [ 9 , 11 , 12 , 14 , 17 ]. Cilostazol is a platelet-aggregation inhibitor and has been administered intrinsically for preventing relapse in patients with cerebral infarction or chronic arterial occlusion.…”
mentioning
confidence: 99%
“…Recent studies have reported the effectiveness of orally administered cilostazol, a phosphodiesterase III inhibitor, in treating bradyarrhythmia in humans and animals [ 9 , 11 , 12 , 14 , 17 ]. Cilostazol is a platelet-aggregation inhibitor and has been administered intrinsically for preventing relapse in patients with cerebral infarction or chronic arterial occlusion.…”
mentioning
confidence: 99%
“…11 In addition, recovery of the AV conduction using cilostazol in a human patient with advanced AV block has been reported. 14…”
Section: Introductionmentioning
confidence: 99%
“…Cilostazol has positive chronotropic effects and has been used to treat human patients with bradyarrhythmias, such as atrioventricular (AV) block and SSS [2, 9, 10, 12, 15, 19]. Cilostazol has also been reported to have long-term chronotropic effects [5, 9].…”
mentioning
confidence: 99%
“…Cilostazol has also been reported to have long-term chronotropic effects [5, 9]. The mechanisms of action of cilostazol include vasodilation resulting in a reflex increase in heart rate (HR), improvement of sinus function by suppression of parasympathetic tone, increased blood flow to the sinus node resulting from coronary artery dilatation, and increased sinus node intracellular cyclic adenosine monophosphate [12]. Cilostazol has been reported to increase the heart rate in experimental dogs [14].…”
mentioning
confidence: 99%
See 1 more Smart Citation